Prognostic Value of Urinary Biomarkers in Proteinuria Progression in IgA Nephropathy Patients Treated with Budesonide - Christodoulos Keskinis; Eleni Moysidou; Stamatia Stai; Michalis Christodoulou; Georgios Lioulios; Sotirios-Spyridon Vamvakas; Maria Stella Trivyza; Panagiotis Pateinakis; Marios Papasotiriou; Maria Stangou (Medicina)
Background & Objectives: Targeted-release budesonide (TRB) is the first approved agent aimed at targeting the early pathogenetic cascade in IgA nephropathy (IgAN). Materials and Methods: This prospective study included Caucasian IgAN patients diagnosed within the last 5 years, who had started a 10-month TRB treatment and were followed in the outpatient clinic. All participants had been on the maximal supportive care dose for at least the previous 6 months. Kidney function and proteinuria levels were recorded at the start of TRB treatment (T0) and at 3, 6, and 10 months (T3, T6, and T10, respectively), while urinary monocyte chemotactic protein-1 (MCP-1), matrix metalloproteinase-9 (MMP-9) and clusterin (CLU) levels were measured at T0 and T3. Results: In the cohort of all patients (mean age 53.24 ± 12.76 years, estimated glomerular filtration rate (eGFR 52.84 ± 25.93 mL/min/1.73 m2, proteinuria 2.84 ± 1.26 g/24 h), significant correlations were observed at T0 between MMP-9 and MCP-1 (r = 0.74, p = 0.004), MMP-9 and uCLU (r = 0.77, p = 0.002), and MCP-1 and uCLU (r = 0.65, p = 0.01). At T3, a significant correlation between MMP-9 and urinary CLU (uCLU) persisted (r = 0.71, p = 0.03). Higher MCP-1 (r = −0.560, p = 0.046) and MMP-9 (r = −0.330, p = 0.012) levels at T0 were associated with reduced proteinuria. Conversely, increased clusterin at T3 (r = 0.599, p = 0.031) was associated with worsening proteinuria. Conclusions: The treatment response to TRB was heterogeneous, with recent diagnosis (RD) patients showing improved kidney function and proteinuria, while older diagnosis (OD) patients exhibited worsening biomarkers and declining kidney function. Therefore, early interventions are crucial in IgAN patients. Finally, the biomarkers studied can be used prognostically to monitor disease progression.